Conservation genetics: Linking science with practice. Issue 17 (2nd September 2019) - Holderegger, Rolf; Balkenhol, Niko; Bolliger, Janine; Engler, Jan O.; Gugerli, Felix; Hochkirch, Axel; Nowak, Carsten; Segelbacher, Gernot; Widmer, Alex; Zachos, Frank E.
Abstract: Conservation genetics is a well‐established scientific field. However, limited information transfer between science and practice continues to hamper successful implementation of scientific knowledge in conservation practice and management. To mitigate this challenge, we have established a conservation genetics community, which entails an international exchange‐and‐skills platform related to genetic methods and approaches in conservation management. First, it allows for scientific exchange between researchers during annual conferences. Second, personal contact between conservation professionals and scientists is fostered by organising workshops and by popularising knowledge on conservation genetics methods and approaches in professional journals in national languages. Third, basic information on conservation genetics has been made accessible by publishing an easy‐to‐read handbook on conservation genetics for practitioners. Fourth, joint projects enabled practitioners and scientists to work closely together from the start of a project in order to establish a tight link between applied questions and scientific background. Fifth, standardised workflows simplifying the implementation of genetic tools in conservation management have been developed. By establishing common language and trust between scientists and practitioners, all these measures help conservation genetics to play a more prominent role in future conservation planning and management.